1996
DOI: 10.1007/bf02093592
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, serological markers, and hepatic disease of anti-HCV ELISA-2-positive blood donors

Abstract: The epidemiology associated with hepatitis C virus (HCV) infection, serologic reactivity, and hepatic disease related to anti-HCV-positive donors of Granada were researched. From 1990 through 1993, medical and epidemiological information and anti-HCV and HCV RNA testing were evaluated in 46,741 blood donors. Serum samples were obtained for anti-HCV ELISA and RIBA and HCV RNA determination. A liver biopsy was conducted in all anti-HCV positives by confirmatory second-generation RIBA to analyze the hepatic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Of the anti-HCV donors tested, 75% were HCV RNA positive. In Italy, in the USA and in Spain the frequency of HCV RNA positivity was 66%, 58% and 63%, respectively, among RIBA-2 positive and indeterminate donors 13,16,20 . In a recent compilation 15 62% of RIBA-2 positive or indeterminate donors were HCV RNA positive, a frequency slightly lower than that observed here among our donors (75%) with an EIA ratio>3 and high positivity for RIBA-2.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Of the anti-HCV donors tested, 75% were HCV RNA positive. In Italy, in the USA and in Spain the frequency of HCV RNA positivity was 66%, 58% and 63%, respectively, among RIBA-2 positive and indeterminate donors 13,16,20 . In a recent compilation 15 62% of RIBA-2 positive or indeterminate donors were HCV RNA positive, a frequency slightly lower than that observed here among our donors (75%) with an EIA ratio>3 and high positivity for RIBA-2.…”
Section: Discussionmentioning
confidence: 95%
“…This proportion is greater than the 36% of RIBA-2 positive cases reported in similar individuals in studies conducted in Italy 16,19 and France 22 and the 39% observed in the USA 13 . In Spain, 33-63% of anti-HCV positive donors were also RIBA-2 positive 17,20 . The discrepancy between our results and these cited above may be related to the type of donor included in our avaliation (EIA ratio >3).…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is greater than the 36% of RIBA-2 positive cases reported in similar individuals in studies conducted in Italy 18,22 and France 24 and 39% observed in USA 11 . In Spain, 33-63% of anti-HCV positive was also RIBA-2 positive 19,23 . The discrepancy between our results and these cited above may be related to the type of donor included in our evaluation (EIA>3 and qALT>1).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to patients with chronic liver disease, only 36% to 65%, anti-HCV (EIA-2) positive blood donors are RIBA positive and 20% to 30% are RIBA indeterminate. The percentage of EIA-2-positive blood donors who have detectable HCV-RNA in serum when tested by RT-PCR varies from 70% to 90% for those who are RIBA positive to 2% to 40% for those who are RIBA indeterminate 18,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Other studies have also reported that only about 80% (range, 73% to 89%) of confirmed anti-HCV positive patients are viremic if tested for HCV-RNA by RT-PCR. [28][29][30] Thus, an HCV infection (HCV-RNA-positive) prevalence of 3.1 million (range, 2.8 to 3.5 million) probably is a more accurate and realistic estimate based on the NHANES III database.…”
Section: Data Sourcesmentioning
confidence: 99%